ANTI-AMERICANISM IN NIKE DREAM CRAZY CAMPAIGN ADVERTISEMENT: A MULTIMODAL ANALYSIS - Diaz Adrian (ELite Journal : International Journal of Education, Language, and Literature, 2022)
This study aims to explore on anti-Americanism portrayed in Nike Dream Crazy advertising, which features the controversial athlete Colin Kaepernick. Using a descriptive qualitative method and systemic-functional approach, Kress and van Leeuwen's (2006) grammar of visual design, which is based on Hallidayan Systemic Functional Linguistics (SFL), was applied to uncover the matter projected through the non-verbal elements. The verbal elements were explained with Searle's speech act. Moreover, Chiozza's formulation of anti-Americanism was applied to bring the analysis to a grand conclusion. The datum for the current study comprises the printed advertisement of Nike Dream Crazy advertising featuring Colin Kaepernick in the form of a digital picture. The finding shows that anti-Americanism in the advertisement is projected by the non-verbal modes and its interplay with the verbal mode through the three metafunctions of SFL.